Physicochemical properties and in vitro osteocompatibility of different titanium surfaces stored in a saline solution - Kai-Ming Tang; Wen-Si Zhang; Yao Liu; Wen-Qing Zhu; Jing Qiu (Materials Research Express, 2021)
Objective . The study aimed to investigate the physicochemical properties of titanium surfaces with different morphologies stored in a saline solution and their effects on osteoblast behavior. Methods . Freshly prepared commercial pure titanium (cp-Ti), acid-etching titanium (SLA-Ti) and nanowire titanium (NW-Ti) were stored in 0.9% and 10% NaCl solutions, and exposure to air and double-distilled water were used as controls. After storage for two weeks, scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), optical contact angle instrument, and optical profilometer were used to analyze the micro-morphology, elemental composition of the samples, contact angle and surface roughness. BCA protein kit was used to detect the protein adsorption capacity of the three titanium surfaces under the different storage conditions. MC3T3-E1 osteoblast-like cells were cultured on the titanium surfaces. The proliferation, adhesion, alkaline phosphatase activity, and osteogenic differentiation of MC3T3-E1 cells were assessed using CCK-8, laser confocal microscope (CLSM), alkaline phosphatase (ALP) assay, and western blotting. Results . SEM results indicated that the storage conditions did not affect the micromorphology of the titanium surfaces. The XPS and contact angle determination results suggested that cp-Ti, SLA-Ti, and NW-Ti stored in NaCl solutions showed less carbon contamination, higher hydrophilicity. The roughness results showed that the air groups and 10% NaCl had higher roughness. The protein adsorption capacity of the three titanium surfaces was significantly improved under storage in 0.9% NaCl. The proliferation activity of osteoblasts on the three titanium surfaces was not different from the control groups after storage in 0.9% NaCl solution. However, the results of the in vitro study suggested that the cell adhesion capacity and the expression of ALP and the osteogenic-related proteins Runx2, Osterix, and Osteocalcin improved after storage in 0.9% NaCl solution. Conclusions . The storage of the different types of titanium surfaces in 0.9% NaCl solution could effectively reduce carbon contamination, maintain good hydrophilicity, improve the roughness and make the environment conducive to the differentiation of osteoblasts.